Crime and safety-related concerns in a small community - Austin, D. Mark (American journal of criminal justice, 1994)
This research utilizes social context and personal characteristics as determinants of both perceptions and satisfaction with safety in the local neighborhood. Using survey data obtained from residents of a small town, this analysis examines the impact of satisfaction with the environment, victimization, and social integration on attitudes concerning safety. Consistent with past research, results indicate that victimization and satisfaction with the local area are both significant predictors of perceptions of safety. They also share a significant relationship with satisfaction with safety. Two indicators of social integration yielded differing results. Participation in local organizations and associations played a more significant role in attitudes concerning safety than did the number of friends a respondent has in the neighborhood. When controlling for personal characteristics, participation in organizations was a more significant predictor of perceptions of safety than of satisfaction with safety.